Perspektif Pendidikan Islam Dalam Pengendalian Bullying di Indonesia - Yusnita, Erni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This ponder explores the viewpoint of Islamic instruction in combating bullying in Indonesia. It is persuaded by the tall frequency of bullying in schools and the require for viable approaches that consolidate devout values. The point of the investigate is to investigate how Islamic instruction standards can be utilized to anticipate and address bullying. The technique incorporates a writing survey of different scholastic sources and interviews with teachers and Islamic professionals from a few schools in Indonesia. The discoveries uncover that Islamic instruction values such as sympathy, equity, and sympathy have noteworthy potential to diminish bullying behaviors. By executing a educational programs centered on character improvement and applying Islamic standards, occurrences of bullying can be altogether diminished. In conclusion, joining Islamic instruction standards into school educational program and arrangements is viable in tending to and anticipating bullying whereas cultivating a more secure and more comprehensive learning environment.